2008
DOI: 10.1007/s00134-008-1320-4
|View full text |Cite
|
Sign up to set email alerts
|

Continued survival gains in recent years among critically ill myeloma patients

Abstract: Hospital mortality decreased significantly over the last 15 years in myeloma patients admitted to the ICU. Risk factors for death were organ failure and poor chronic health status. Early ICU admission was associated with lower mortality, suggesting opportunities for further improving survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
75
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 31 publications
2
75
0
4
Order By: Relevance
“…Previous studies of patients with hematological malignancies and sepsis or septic shock showed improved outcomes as a result of earlier treatment of organ failures. 6,31,32 Conceivably, understanding early predictors of invasive mechanical ventilation would improve mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of patients with hematological malignancies and sepsis or septic shock showed improved outcomes as a result of earlier treatment of organ failures. 6,31,32 Conceivably, understanding early predictors of invasive mechanical ventilation would improve mortality.…”
Section: Discussionmentioning
confidence: 99%
“…24,29 More recently, outcomes have improved. 6,31,32 In this study, subjects who received early or prophylactic NIV (ie, NIV trial in a subject without any intubation criteria and no other organ failure) were not distinguished from subjects who received curative NIV (ie, NIV trial in a subject with intubation criteria or asso- ciated organ failure). The number of analyzed subjects treated with NIV was limited in this study, so we cannot draw definite conclusions from this set of data.…”
Section: Discussionmentioning
confidence: 99%
“…These studies highlighted not only the beneficial impact of advances in critical care and in hematology and oncology, but also the inadequacy of our triage criteria [12]. Furthermore, they have established that a crucial goal is the early management (and even prevention) of organ dysfunction [13,14].…”
mentioning
confidence: 99%
“…Three elements have been perfectly demonstrated. The first is that the prognosis of patients suffering from MM requiring ICU admission improves over the years, probably in relation to the existence of new therapies [7]. The second is that the duration of treatment of 1 month is far too short to presume the recovery or not or to determine the renal function to avoid dialysis.…”
mentioning
confidence: 97%